ANALISIS KONDISI CAMPUR KODE DAN ALIH KODE BAHASA PADA MAHASISWA PRODI BAHASA MANDARIN FKIP UNTAN 2019 - Agnes Zoan; Lily Thamrin; Lusi Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
Students of the Mandarin Language Education Study Program FKIP Untan 2019 are bilingual and even multilingual, resulting in language phenomena appearing in their communication process called code-mixing and code-switching. To find out the conditions of code-mixing and code-switching among students, the authors used observation and interview research methods. Based on the results of observations and data analysis, code-mixing carried out by students in 109 conversations included: external code-mixing, internal code-mixing, and mixed code mixing at the word, phrase, and clause level. In conversation, students inserted Indonesian, Mandarin, English, Malay, Dayak, Hakka, and Teochew language. There are 7 factors that cause code-mixing, namely the speech partner; communication needs; habit; ease and clarity of communication; making sure of something; language barriers, and use of popular terms. In addition to code-mixing, it was found that code-switching occurred in 26 conversations including external code-switching and internal code-switching. In conversation, there are several languages switching, namely Indonesian-Mandarin, Indonesian-Hakka, Mandarin-Teochew, and Mandarin-Indonesian code-switching. There are 5 factors that cause code-switching, namely unequal bilingual ability; speech partner; request; the need to convey information, and the desire to use Mandarin as much as possible.